2020
DOI: 10.3390/app10051634
|View full text |Cite
|
Sign up to set email alerts
|

Research on Static and Dynamic Characteristics of Gas-lubricated Microbearings for Microfluidic Devices

Abstract: Aerodynamic journal microbearings with microtribological phenomena significantly influence the operating stability of microfluidic devices. The modified Reynolds equations including different rarefaction models are derived and are solved by the partial derivative method and relaxation iteration algorithm. The effects of Knudsen number and bearing parameters on the static and dynamic characteristics of microbearings are investigated in detail. The results show that the rarefaction effect plays a crucial role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Due to its lower calculation cost and higher precision, the FK model had been applied in various cases. In recent years, by using the FK model, some scholars [16,17] have found that the rarefaction effect has a large influence on the load capacity and attitude angle of MEMS bearing compared with those in the continuous model.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its lower calculation cost and higher precision, the FK model had been applied in various cases. In recent years, by using the FK model, some scholars [16,17] have found that the rarefaction effect has a large influence on the load capacity and attitude angle of MEMS bearing compared with those in the continuous model.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the wind power bearings mainly work in the plateau, grassland air thinning, and other areas, studying the gas lubrication micro-bearing microfluidic control device can provide a reliable research basis for wind power bearings. WU et al [194] modeled the journal micro-bearing (Figure 14), derived the modified Reynolds equation for the sparse model under different conditions, and carried out a detailed study on the parameters of the micro-bearing and the Knudsen number to conclude that when the Knudsen number is less than 0.325, the sparse gas can form a thin lubrication film on the surface of the non-stop-running journal micro-bearing, which can reduce the friction coefficient and bear the bearing load significantly. Due to the wind power bearings mainly work in the plateau, grassland air thinning, and other areas, studying the gas lubrication micro-bearing microfluidic control device can provide a reliable research basis for wind power bearings.…”
Section: Research and Analysis Of Wind Power Bearing Lubrication Base...mentioning
confidence: 99%
“…Bearing gas lubrication structure diagram and three-dimensional view. (a) Schematic view; (b) 3D graphical representation[194].…”
mentioning
confidence: 99%